A calcium phosphate coated biphasic scaffold for periodontal complex regeneration - Vaquette, C. (2012)
Periodontitis is a common infectious disease that results in the degradation of the supporting tissues around teeth, which if left untreated can lead to tooth loss in the later stages of the disease. We have developed a biphasic scaffold for simultaneous regeneration of the alveolar bone and the periodontal ligament (PDL). This study represents a step forward into the optimization of this scaffold by utilizing a fused deposition modeling scaffold coated by a calcium phosphate layer for the bone compartment whereas the periodontal compartment consisted of a melt electrospun scaffold onto which PDL cell sheets were placed. Both the in vitro and in vivo performances of this biphasic scaffold were evaluated and it was observed that the alkaline phosphatase activity was significantly higher for the CaP coated samples and that the coated scaffolds displayed higher mineralization volume than the non-coated group. The scaffolds were placed onto a dentin block and implanted in a rodent subcutaneous model for 8 weeks, and higher bone formation was observed for the coated scaffolds. Histological analysis revealed that the large pore size of the periodontal compartment permitted the vascularisation of the cell sheets and a PDL-like tissue was observed at the dentine interface. This work demonstrates that the combination of cell sheet technology together with an osteoinductive biphasic scaffold could be utilized to address the limitations of current periodontal regeneration techniques.